Protective effect of black seed nigella sativa (l.) Against cyclophosphamide-induced toxicity on reproductive and acrosomal function in mice - Abdul Rahman, Suzanah; Kamarzaman, Saheera; Shaik , Sadak Basha; Shaik Dawood, Noor Faridah (IDOSI Publications, 2013)
To determine the effect of ethanol extract of Nigella sativa on cyclophosphamide reproductive toxicity and acrosome function of sperm. Male Balb/c mice, aged between 5 to 7 weeks were divided into four groups, each of six animals. Cyclophosphamide was administered via intraperitoneal injection at 200 mg/kg body weight and ethanol extraction of Nigella sativa was similarly injected at a dose of 10 mg/kg and continued on alternate days for the duration of 32 days. All mice were sacrificed on day 33 and testes and epididymides were excised. Group I served as control while group II was treated with cyclophosphamide and group III with 10 mg/kg of Nigella sativa and group IV with a combination of cyclophosphamide and Nigella sativa at the same concentrations. Effects of cyclophosphamide include reduction of weights of testes, epididymides and sperm count. A higher value of sperm count was observed in the cyclophosphamide plus Nigella sativa group when compared to the cyclophosphamide alone group, perhaps indicating the medicinal plant antioxidant properties in the germ cell line. Treatment with cyclophosphamide led to a high percentage of acrosome reacted sperm possibly to spontaneous acrosomal reaction caused by free radicals. Although the combination treatment seemed to show similar histology to the effects of cyclophosphamide alone, a protective outcome was indicated with the higher number of sperm count with the addition of Nigella sativa. Paradoxical effects of Nigella sativa were observed on the cells in the testis and acrosome reaction including in the protection against oxidative agents and alkylating effects of cyclophosphamide. Further investigation is recommended to determine outcomes in the presence of oocytes, at the time when sperm capacitation and acrosome reaction usually occur.